2017
DOI: 10.1111/jpn.12616
|View full text |Cite
|
Sign up to set email alerts
|

Cholelithiasis in adult bearded dragons: retrospective study of nine adult bearded dragons (Pogona vitticeps) with cholelithiasis between 2013 and 2015 in southern Germany

Abstract: SummaryWith an increased number of pet reptiles, many diseases occur due to nutritional disorders. Between 2013 and 2015, irregular gallbladder contents (sludge/choleliths) in adult bearded dragons (Pogona vitticeps) were recorded in many of the routinely conducted necropsies at the reptile rescue station in Munich (Auffangstation f€ ur Reptilien, M€ unchen e.V., Munich, Germany). Nine animals, six from the rescue station and three from an associated veterinary practice (Tier€ arztliche Praxis f€ ur Exoten, Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…The true prevalence of choleliths in bearded dragons is currently unknown. This condition has been reported in seven adult bearded dragons (one individual in Ritzman and Garner [2009]; six of nine individuals in Gimmel et al [2017]), in addition to the two cases presented herein.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…The true prevalence of choleliths in bearded dragons is currently unknown. This condition has been reported in seven adult bearded dragons (one individual in Ritzman and Garner [2009]; six of nine individuals in Gimmel et al [2017]), in addition to the two cases presented herein.…”
Section: Discussionsupporting
confidence: 71%
“…Postmortem evaluation was necessary to identify irregular gallbladder contents such as sludge and choleliths in eight of nine adult bearded dragons in a previous study, whereas the antemortem sonographic evaluation revealed a gallbladder cholelith in only one individual (Gimmel et al, 2017). Cholecystolith was present in 6 of 9 cases, sludge in 3 of 9 cases, and both cholecystolith and sludge in 1 of 9 cases.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations